Future methane fluxes of peatlands are controlled by management practices and fluctuations in hydrological conditions due to climatic variability - Tyystjärvi, Vilna; Markkanen, Tiina; Backman, Leif; Raivonen, Maarit; Leppänen, Antti; Li, Xuefei; Ojanen, Paavo; Minkkinen, Kari; Hautala, Roosa; Peltoniemi, Mikko; Anttila, Jani; Laiho, Raija; et al. (Copernicus Publications, 2024)
Peatland management practices, such as drainage and restoration, have a strong effect on boreal peatland methane (CH4) fluxes. Furthermore, CH4 fluxes are strongly controlled by local environmental conditions, such as soil hydrology, temperature and vegetation, which are all experiencing considerable changes due to climate change. Both management practices and climate change are expected to influence peatland CH4 fluxes during this century, but the magnitude and net impact of these changes is still insufficiently understood. In this study, we simulated the impacts of two forest management practices, rotational forestry and continuous cover forestry, as well as peatland restoration, on hypothetical forestry-drained peatlands across Finland using the land surface model JSBACH (Jena Scheme for Biosphere–Atmosphere Coupling in Hamburg) coupled with the soil carbon model YASSO and a peatland methane model HIMMELI (Helsinki Model of Methane Buildup and Emission for Peatlands). We further simulated the impacts of climatic warming using two RCP (Representative Concentration Pathway) emission scenarios, RCP2.6 and RCP4.5. We investigated the responses of CH4 fluxes, soil water-table level (WTL), soil temperatures and soil carbon dynamics to changes in management practices and climate. Our results show that management practices have a strong impact on peatland WTLs and CH4 emissions that continues for several decades, with emissions increasing after restoration and clearcutting. Towards the end of the century, WTLs increase slightly, likely due to increasing precipitation. CH4 fluxes have opposing trends in restored and drained peatlands. In restored peatlands, CH4 emissions decrease towards the end of the century following decomposition of harvest residue in the top peat layers despite increasing WTLs, while in drained peatland forests sinks get weaker and occasional emissions become more common, likely due to rising WTLs and soil temperatures. The strength of these trends varies across the country, with CH4 emissions from restored peatlands decreasing more strongly in southern Finland, and forest soil CH4 sinks weakening most in northern Finland.
Keywords: methane; peatland forests; peatlands; climate changes; forest management; ennallistaminen; metaani; suometsät; suot; ilmastonmuutokset; hakkuut; metsätalous; mallintaminen; hydrologia; hydrology